Rekomendasi Iphone Bagi Pembeli Baru Di Appel House Store Yogyakarta Dengan Metode WP - Tarigan, Daniel Praise (JATISI, 2024)
In the current digital era, where technological devices have become an inseparable part of everyday life, especially in the use of mobile phones or gadgets, research on iPhone recommendations for new buyers at the Appel House Store Yogyakarta using the Weighted Product (WP) method has significant importance. . This method was chosen because of its ability to consider criteria such as RAM, price, ROM, screen and battery, thereby providing more precise and personalized recommendations for new buyers. Data from new buyers is analyzed using WP to determine which iPhone best suits their preferences. The results show that WP is effective in providing recommendations that match buyer preferences, providing a useful guide for new buyers in choosing an iPhone at the Appel House Store Yogyakarta. The importance of this research is to improve the experience of new buyers in choosing an iPhone according to their needs and preferences.